Análisis del tratamiento informativo sobre Richard Carapaz en fan page del diario The Guardian-UK, periodo abril-septiembre 2021. - Palacios Jara, Estefanny Michelle (2025)
The present research analyzes Richard Carapaz's informative treatment of The Guardian-UK newspaper's fan page from April to September 2021. Talking about sports journalism has become an informative instrument of great social significance, going from knowing almost no information to being the most desired and used in many countries worldwide, especially in countries in Europe and Latin America; this branch of communication is desired by several sports fans who work or wish to work, both in the written press and in the media television, radio, and especially in this new digital era where all information is transmitted through the different existing digital media. A mixed type of research is used, with analytical and qualitative-quantitative methods. In the case of qualitative research, the contents displayed on the fan page of the newspaper The Guardian-UK are analyzed. The results demonstrated that the news published about Richard Carapaz was written by following the guidelines of sports journalism, answering the questions when, how, where, what, why, and giving the necessary highlight to the athlete.